PERANCANGAN DISKRIT D FLIP-FLOP MENGGUNAKAN TEKNOLOGI CMOS 0.35 µm - Widyastuti Widyastuti; Hamzah Afandi; Ganjar Febriyani Pratiwi (Universitas Muhammadiyah Semarang, 2018)
Accumulator dump is one of the tools used to convert serial data into parallel data on RFID communications. Accumulator dump on RFID communication consists of a series of counters and registers, where one of the supporting circuits in the counter and register is D flip-flop. D flip-flops are one type of flip-flop that is built using RS flip-flops. Discrete circuit design Master-slave flip-flops are built using NAND logic gates built using 0.35 µ m CMOS technology. The results of the D flip-flop circuit design are simulated using LT- SPICE software to see the speed of response and power dissipation in the circuit. Keywords: RFID, CMOS 0.35 µ m, D flip-flop, Dump Accumulator, NAND logic